Bending of thin-walled tubes - Ng, Anna Tian Yun (Nanyang Technological University, 2024)
This study delves into the examination of thin-walled tube behavior under pure bending conditions. A specially designed four-point bending test rig was meticulously crafted to conduct experiments on thin-walled tubes composed of various materials, with a primary focus on 304 Stainless Steel. The Instron Universal Testing Machine served as the apparatus for applying an incremental load to the tubes, leading to deformation until the yield load was attained. The experimental data obtained from these tests facilitated the determination of the tubes' yield strength, utilizing the 0.2% strain criterion. Comparative analyses were performed among tubes of varying sizes and wall thicknesses to explore alterations in flexural strength and yield points. Notably, thicker tube walls demonstrated an enhanced capacity to withstand applied loads and exhibited greater bending moments in comparison to thinner tube walls. The deflection behaviors of the tubes were observed to be similar. The experimental results were compared with theoretical values. The difference between the values were attributed to a misalignment issue which occurred during the bending process. Additionally, the loads on the Test Fixture’s linear guide exceeded its maximum loading capacity. The outcomes of this study carry substantial implications for the utilization of thin-walled tubes in engineering applications. Understanding the performance variations based on size and wall thickness is crucial for optimizing structural designs and ensuring the reliability of thin-walled tubes in real-world engineering scenarios. The identified limitations in experimental procedures also emphasize the need for meticulous attention to alignment and loading capacity considerations in future investigations.